Psy-tech Fusion: The psychology behind modern technology - Vallas, Angelos; Tsipotis, Giannos (Open Schools Journal for Open Science, 2024)
This project examines the psychological tricks used by social media companies to influence users and their impact on mental health. Techniques such as the frequency illusion, Fear of Missing Out (F.O.M.O.), emphasis on the human element, social proofing, exposure effect, and color psychology exploit cognitive biases and emotions, often leading to negative outcomes like social isolation, cyberbullying, reduced attention spans, and technology addiction. Despite these challenges, technology can also enhance connectivity and provide valuable mental health resources. Understanding these psychological strategies is crucial for mitigating their negative effects and promoting mental well-being in the digital age.